STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI DALAM KETERKAITAN PERTUMBUHAN PERUSAHAAN DENGAN PROFITABILITAS: STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI DALAM KETERKAITAN PERTUMBUHAN PERUSAHAAN DENGAN PROFITABILITAS - I Made Purba Astakoni; I Wayan Wardita (STIMI Handayani Denpasar, 2018)
The purpose of this study are (1) Analyze and explain the effect of companygrowth on profitability (profitability) at PT. Mustika.Ratu and Subsidiaries; (2)Analyze and explain the influence of company growth on capital structure at PT.Mustika.Ratu and Subsidiaries; (3) Analyze and explain the influence of capitalstructure on profitability at PT. Mustika.Ratu and Subsidiaries (4) Analyzing therole of capital structure in mediating the relationship of company growth withprofitability at PT. Mustika.Ratu and Subsidiaries. Data analysis technique usingPartial Least Square (PLS) approach. The results of the first hypothesis testingobtained that the growth rate of the company (company growth) significantly negatively affect the capital structure at PT. Mustika Ratu and Subsidiaries. Results of testing the second hypothesis; obtained that the growth of company(company growth) have a significant positive effect on profitability at PT.Mustika Ratu and Subsidiaries. Results of testing the third hypothesis; obtainedthat capital structure of company (capital structure) have a significant negativeeffect on profitability at PT. Mustika Ratu and Subsidiaries. Also the capitalstructure is able to mediate the relationship between firm growth and profitability.